1998
DOI: 10.1002/(sici)1098-2795(199805)50:1<93::aid-mrd12>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Expression of germ cell nuclear factor (GCNF/RTR) during spermatogenesis

Abstract: Germ cell nuclear factor (GCNF/RTR), a novel orphan receptor in the nuclear receptor superfamily of ligand-activated transcription factors, is expressed predominantly in developing germ cells. In several mammalian species two GCNF/RTR mRNAs are present in the testis, with the smaller 2.3-kb transcript generally expressed at higher levels than the larger 7.4- or 8.0-kb transcript. In both the mouse and rat, the 2.3- and 7.4-kb GCNF/RTR transcripts were detected in isolated spermatogenic cells, but not in Sertol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…PAF-1 is thought to be a novel orphan receptor in the nuclear receptor superfamily of ligand-activated transcription factors. In addition, TAK1 (Hirose et al 1994(Hirose et al , 1995b, Tr2-11 (CH Lee et al 1996), and Germ cell nuclear factor/retinoid receptor-related testis-associated receptor (GCNF/RTR) (Chen et al 1994;Hirose et al 1995a;Zhang et al 1998) are orphan receptors that have been demonstrated in testis of mouse (Chen et al 1994;Hirose et al 1995a) and man (Süsens and Borgmeyer 1996;Lei et al 1997). Like PAF-1, GCNF/RTR is expressed in round spermatids, but declines abruptly as spermatids start to elongate.…”
Section: Cre-boxmentioning
confidence: 99%
“…PAF-1 is thought to be a novel orphan receptor in the nuclear receptor superfamily of ligand-activated transcription factors. In addition, TAK1 (Hirose et al 1994(Hirose et al , 1995b, Tr2-11 (CH Lee et al 1996), and Germ cell nuclear factor/retinoid receptor-related testis-associated receptor (GCNF/RTR) (Chen et al 1994;Hirose et al 1995a;Zhang et al 1998) are orphan receptors that have been demonstrated in testis of mouse (Chen et al 1994;Hirose et al 1995a) and man (Süsens and Borgmeyer 1996;Lei et al 1997). Like PAF-1, GCNF/RTR is expressed in round spermatids, but declines abruptly as spermatids start to elongate.…”
Section: Cre-boxmentioning
confidence: 99%
“…Gcnf transcription is confined to germ cells in both the testis and ovary [1,2]. In males Gcnf transcription occurs at lower levels during the meiotic prophase in rats and mice [4] and increases substantially in postmeiotic germ cells, with maximum levels in stage VI-VIII round spermatids [4,5]. In female mice Gcnf mRNA is present in growing oocytes, but it is undetectable in oocytes within primordial follicles [5].…”
Section: Introductionmentioning
confidence: 99%
“…Only the larger 7.4 kb Gcnf transcript has been identified in mouse embryos [7], embryonal carcinoma cell lines [20], and in some somatic tissues at significantly lower levels [1,21]. In contrast, spermatogenic cells express both 7.4 and 2.1 kb Gcnf transcripts [2,4,5]. The 7.4 kb transcript is expressed earlier during testicular development and is the predominant Gcnf mRNA in pachytene spermatocytes [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations